2009
DOI: 10.1243/09576509jpe793
|View full text |Cite
|
Sign up to set email alerts
|

Numerical investigation of the unsteady behaviour of tip clearance flow and its possible link to stall inception

Abstract: Three-dimensional unsteady calculations were performed to explore the unsteady nature of tip clearance flow and its possible linking with the spike stall inception. It was found that the interaction of the broken-down leakage vortex with the tip clearance flow formed another distinctive vortex, denoted as the tip separation vortex. It formed below the rotor blade tip section and propagated diagonally inward. This vortex propagated across the rotor passage from the pressure side to the suction side with its vor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2014
2014
2025
2025

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 27 publications
(13 citation statements)
references
References 23 publications
0
13
0
Order By: Relevance
“…Due to its great impacts on compressors, flow unsteadiness has drawn the attention of a large number of researchers [7][8][9][10][11][12][13][14][15][16][17][18][19]. The knowledge reported to date allows the flow unsteadiness to be divided into three categories; TLV breakdown, shock interaction and self-induced unsteadiness.…”
Section: List Of Abbreviationsmentioning
confidence: 99%
“…Due to its great impacts on compressors, flow unsteadiness has drawn the attention of a large number of researchers [7][8][9][10][11][12][13][14][15][16][17][18][19]. The knowledge reported to date allows the flow unsteadiness to be divided into three categories; TLV breakdown, shock interaction and self-induced unsteadiness.…”
Section: List Of Abbreviationsmentioning
confidence: 99%
“…Study on the endwall flow evolving into the passage is not only an impor tant but also a difficult issue in the past few years. The stable operating range of axial compressors, especially "tip-critical compressors" [10][11][12] influenced tremendously by tip clearance size. In addition, shock wave establishes in transonic flows, which will incite interactions of shock wave and other flows [2,3].…”
Section: In V E S Tig a Tio N S On Th E E Ffects Of In Flo W C O N D mentioning
confidence: 99%
“…3) The formation and development of the tip secondary vortex(TSV). Numerical simulation and experiments have been conducted on a single subsonic rotor by Wu et al (2010Wu et al ( , 2012. The research showed that TLV breakdown on the near stall condition and a tip secondary vortex originated from the interaction between the main flow and the tip leakage flow.…”
Section: Introductionmentioning
confidence: 99%